Current challenges of mining investment in Peru: Interview with Dr. Luis Carlos Rodrigo Prado - Terrazas Cosio, Bresia Rosalid (2014)
In this interview, our guest responds to current and controversial issues related to environmental matters and the mining sector. First, the author talks about the variability of numbers for investment in mineral exploration in our country along recent periods. Also, the problem of social unrests, tax issues, permits and licenses, known as «permisología» and their impact on the sector. Similarly, and inevitably, some comment on the widespread use of Contracts Tax Stability and new measures of environmental control, taken by the recently enacted and controversial Law N° 30230 – Law Establishing Tax Measures, Simplification of Procedures and permits for promotion and revitalization of investment in the country, also called «Paquetazo Castilla». Furthermore, about the EIA and the recent creation of SENACE, as part of the Ministry of Environment Agency is analyzed. Finally, our interviewee continues to review the controversial «contribution by regulation» to OEFA and disciplinary proceedings.